FACTORS ASSOCIATED WITH DYNAPENIA IN OLDER ADULTS IN THE NORTHEAST OF BRAZIL - Lucas dos Santos; Rizia Rocha Silva; Pabline dos Santos Santana; Paulo da Fonseca Valença Neto; Cláudio Bispo de Almeida; Cezar Augusto Casotti (Journal of Physical Education)
ABSTRACT This study identified factors associated with dynapenia in older adults residing in a small town in northeastern Brazil. It is a population-based study conducted with 208 senior citizens (58.7% women) from Aiquara, BA. Sociodemographic, behavioral and health information were obtained from face-to-face interviews, and nutritional status was assessed by body mass index. To measure their level of physical activity and sedentary behavior, the International Physical Activity Questionnaire was used. Dynapenia was diagnosed by sex, from the 25th percentile of handgrip strength, by means of a hydraulic dynamometer. For inferential analyses, Poisson regression was used, with a robust estimator, calculation of Prevalence Ratios (PRs) and their respective 95% Confidence Intervals (CIs). The prevalence of dynapenia was higher in older adults aged 70-79 (PR: 3.21; 95%CI: 1.55-6.64) and ≥80 years (PR: 4.91; 95%CI: 2.32-10.39), in those with low weight (PR: 2.20; 95%CI: 1.26-3.82), in those who are insufficiently active (PR: 1.99; 95%CI: 1.12-3.54), and among those with high level of sedentary behavior (PR: 1.88; 95%CI: 1.19-2.98). The factors identified as being associated with dynapenia were: age between 70 and 79 and ≥80 years, insufficient level of physical activity; high level of sedentary behavior, and low weight.